The Marriage Life Experiences and Perceptions on The Early Years of The Marriage: Problems, Difficulties and Needs - Sare Terzi İlhan; Şerife Işık (Anı Publishing, 2019)
The purpose of this study is examining married life experiences and pre-marriage training needs of individuals who have been married for 1-5 years. The research design is phenomenology. The study group consists of 10 married individuals. The study group was formed using purposive sampling method. In collection of data, "Semi-structured Interview Form" were used. For date analysis, content analysis was used. The research findings are below: The newlyweds are provide for proximity, loving/being love, belonging, support, trust, social approval needs through marriage. They have difficulty in the fields of regulation the post-marital life and adaptation to living together. They adapt to post-marital life through understanding, giving time, support. They want to have knowledge about sexuality, relationships with spouse and families before marriage. It is necessary that pre-marriage training programme contain the subject of relationships with spouse, preparing to marriage life, sexuality; the method of this programme can be workshop and applied.